Recurrent intussusception in children and infants - Amine Ksia; Sana Mosbahi; Mohamed Ben Brahim; Lassaad Sahnoun; Besma Haggui; Sabrine Ben Youssef; Kais Maazoun; Imed Krichene; Mongi Mekki; Mohsen Belghith; Abdellatif Nouri (Wolters Kluwer Medknow Publications, 2013)
Background: Recurrent intussusceptions in child and infants are problematic and there are controversies about its management. The aim of this study is to determine the details of the clinical diagnosis of recurrent intussusception and to determine the aetiology of recurrent intussusceptions. Patients and Methods: It's a retrospective study of 28 cases of recurrent intussusception treated in the paediatric surgery department of Monastir (Tunisia) between January 1998 and December 2011. Results: During the study period, 505 patients were treated for 544 episodes of intussusception; there were 39 episodes of recurrent intussusceptions in 28 patients; the rate of patients with recurrence was 5.5%. With comparison to the initial episode, clinical features were similar to the recurrent episode, except bloody stool that was absent in the recurrent group (P = 0,016). Only one patient had a pathologic local point. Conclusion: In recurrent intussusception, patients are less symptomatic and consult quickly. Systematic surgical exploration is not needed as recurrent intussusceptions are easily reduced by air or hydrostatic enema and are not associated with a high rate of pathologic leading points.